The finitude of life—How mortality salience affects consumer behavior: A review - Friederike Gobrecht; André Marchand (Journal of Consumer Behaviour, 2022)
The influence of mortality salience (MS) on consumer behavior has been well-established over the last 250.167emyears. However, research findings have provided divergent insights with regard to the direction of its outcomes. This article provides a systematic review of the extant research stream thereby revealing how the differences are primarily due to the conceptualization and operationalization of MS. Based on a conceptual revision of MS, we suggest an extended definition of the concept. An extensive overview of empirical findings, together with a holistic presentation of influential factors, offers a foundation for further MS studies conducted in a consumer behavior context, concluding with an extensive research agenda.
Keywords: 320